Agrarian Reform for Indigenous Peoples: Conflicts and Redistribution Policies in Senama Nenek Village, Riau - Dwijananti, Bunga Mareta (Sekolah Tinggi Pertanahan Nasional, 2023)
The conflict between the indigenous people of Kenegerian Senama Nenek and PTPN V/PT Perkebunan Negara (State Owned Enterprises/Badan Usaha Milik Negara-BUMN) has been going on for decades. Researchers' document studies and interviews have revealed that the Senama Nenek community's customary land was under PTPN V's unilateral control, which resulted in the loss of the community's customary land forest. The Kampar District Government and the Riau Provincial Government facilitate efforts to resolve the conflict through the courts (litigation) or outside the court (non-litigation), which involve relevant agencies. The conflict was declared resolved in May 2019 through a Limited Meeting Decision on the Acceleration of Settlement of Land Issues led by President Joko Widodo. The final decision was that the 2,800 ha of land was handed over in the form of individual ownership certificates to 1,385 indigenous peoples of the Kenegerian Senama Nenek and then followed up by cooperation with PTPN V with the Partnership Pattern